Hyperthermic intraoperative intrapleural chemotherapy and surgical cytoreduction as part of multimodal treatment of malignant pleural mesothelioma - case report M. Szkorupa1, D. Klos1, J. Chudacek1, J. Hanuliak1, M. Stasek1, O. Fischer2, R. Lemstrova3 - Chemotherapy, Hyperthermic Intraoperative Intrapleural; Report, Surgical Cytoreduction As Part Of Multimodal Treatment Of Malignant Pleural Mesothelioma-Case; Szkorupa, M; Klos, D; Chudacek, J; Hanuliak, J; Stasek, M; Fischer, O; Lemstrová, R (Rozhledy v chirurgii, 2020)
Malignant pleural mesothelioma is one of the most aggressive malignancies with a very poor prognosis. Multimodal treatment consisting of three modalities - chemotherapy, radiotherapy and cytoreductive surgery is optimal. The use of new therapeutic modalities, such as hyperthermic intraoperative intrapleural chemotherapy or photodynamic therapy can improve the current results of mesothelioma treatment. Combined hyperthermic intraoperative chemotherapy and cytoreductive surgery as part of multimodal therapy of malignant mesothelioma has been used since 2017 at the 1st Department of Surgery of University Hospital Olomouc. The authors report the case of a 47-year-old man with malignant epithelioid mesothelioma of the left pleural cavity. Following neoadjuvant chemotherapy, this patient underwent extrapleural pneumonectomy with intraoperative intracavitary hyperthermic chemotherapy. The postoperative period was complicated by circulatory instability and later by tension fluidothorax with signs of heart failure. Currently, 8 months have elapsed from the surgery and the patient remains without any signs of recurrence.
Keywords: pneumektomie; Mesothelioma; Pneumonectomy; Cisplatin; Middle Aged; cisplatina; mužské pohlaví; cytoredukční chirurgie; Neoplasm Recurrence, Local; lokální recidiva nádoru; kombinovaná terapie; nádory pleury; Humans; mezoteliom; Cytoreduction Surgical Procedures; lidé středního věku; Combined Modality Therapy; Pleural Neoplasms; lidé; Male